Identifying the Entrepreneurship Characteristics of the Oil Palm Community Plantation Farmers in the Riau Area - Asmit, Brilliant; Koesrindartoto, Deddy P. (Gadjah Mada International Journal of Business, 2015)
Oil palm is an essential and strategic commodity in the Riau area because of its considerable role in supporting the peoplesâ economy, especially for plantation farmers. Oil palm plantation activities have brought economic impacts to society there, both for the people who are directly involved with the plantations and for their surrounding communities. This regional advantage is a facility for farmers to be able to develop their farms as plantations. The aims of this research are to identify the entrepreneurship characteristics of the oil palm farmers, and also to identify the entrepreneurship characteristics that differentiate the farmers, as seen from their businessâ achievements. The research used a grounded theory approach to identify the characteristics of oil palm farmers systematically. The sampling method used for the research was theoretical sampling, which is data gathering driven by the concepts derived from the theory of previous entrepreneurship characteristics studies. The research object is the oil palm farmers in Riau, Indonesia. The results of the analysis identified the entrepreneurship characteristics of the oil palm farmers, they are growth oriented, risk-taking, innovative, with a sense of personal control, self confident, and cooperative. But, among the characteristics, only the characteristic of their cooperation did not differentiate the oil palm farmers in the achievement of their business activities.